Economic impact of malignant mesothelioma in Italy: an estimate of the public and social costs - Buresti, Giuliana; Colonna, Fabrizio; Corfiati, Marisa; Valenti, Antonio; Persechino, Benedetta; Marinaccio, Alessandro; Rondinone, Bruna Maria; Iavicoli, Sergio (La Medicina del Lavoro, 2017)
Background: Despite their considerable interest for public health policies and for occupational disease management and assessment, the economic costs of asbestos-related diseases (ARDs) for society have not been fully estimated or even frequently discussed. Objectives: The aim of this study was to estimate the economic burden of mesothelioma in Italy by assessing the overall societal cost of the disease, applying an econometric model. Methods: We analyzed two main cost groups, public and social. The first includes expenditure borne by the State and other public bodies (medical care costs, insurance, tax and benefits), while the latter uses the human capital approach to measure the loss of productivity suffered by the economy as a whole. Results: We provide an estimate of € 33,000 per patient for medical care costs and € 25,000 for insurance and compensation; tax and benefits seem to roughly compensate. We estimated a loss of more than € 200,000 per patient, in terms of loss of production. Conclusions: This study offers a practical approach for estimating the economic impact of mesothelioma, and provides empirical evidence of the huge economic burden linked to this disease, with its high etiologic fraction.